2020
DOI: 10.1097/corr.0000000000001569
|View full text |Cite
|
Sign up to set email alerts
|

How Do Medical Students Perceive Diversity in Orthopaedic Surgery, and How Do Their Perceptions Change After an Orthopaedic Clinical Rotation?

Abstract: Background A diverse physician workforce improves the quality of care for all patients, and there is a need for greater diversity in orthopaedic surgery. It is important that medical students of diverse backgrounds be encouraged to pursue the specialty, but to do so, we must understand students’ perceptions of diversity and inclusion in orthopaedics. We also currently lack knowledge about how participation in an orthopaedic clinical rotation might influence these perceptions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 26 publications
1
54
2
Order By: Relevance
“…Second, the current study surveys the perceptions of medical students a medical school in the Kingdom of Saudi Arabia, which could have been influenced by the social practices of the region or population. Such differences are evident from past studies on regional gender variations in surgical specialties [ 16 , 17 ]. Thus, female orthopaedic career opportunities may be skewed by the different issues of different regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the current study surveys the perceptions of medical students a medical school in the Kingdom of Saudi Arabia, which could have been influenced by the social practices of the region or population. Such differences are evident from past studies on regional gender variations in surgical specialties [ 16 , 17 ]. Thus, female orthopaedic career opportunities may be skewed by the different issues of different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Bucknall et al [ 3 ], in a survey of medical students, noted that most students were told by experienced professionals that female surgeons and family life should never coincide, and few were told that only men should undertake surgery as women did not possess skills and strength to competently operate. In a recent study by Rahman et al [ 16 ], the authors compared the perceptions regarding diversity and inclusion among different demographic groups of medical students, which included genders, races or ethnicities, and sexual orientations. The authors found a general improvement in all demographic groups concerning the students’ perception regarding diversity and inclusiveness after orthopaedic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with before their rotation, after their rotations women believed less that they would have to work harder than others to be valued equally on the rotation and thought orthopaedic surgery friendlier, more diverse and less sexist. However, they were still less likely than men to want to pursue a career in orthopaedic surgery ( 24 ). This suggests that, contrary to our study and the study by Baldwin et al, but in keeping with the Perry initiative, orthopaedic exposure may be valuable in improving perceptions of orthopaedics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies detailing associations among orthopaedic institutions’ faculty diversity, resident diversity, and the diversity of the applicant pool of medical students suggest the perception of diversity is an important factor. 27 , 28 , 36 , 48 Additional investigation of these topics is warranted, for which our initial study may serve as a benchmark and impetus for increased participation from professional leagues, allowing for more robust data collection in future iterations.…”
Section: Discussionmentioning
confidence: 99%